Fuzzy congruences on groups and rings - Marouf A. Samhan; T. M. G. Ahsanullah (International Journal of Mathematics and Mathematical Sciences)
We prove that the lattice of fuzzy congruences of a group G (resp. ring R) is isomorphic to the lattice of fuzzy normal subgroups of G (resp. fuzzy ideals of R).